Expression and prognostic value of putative cancer stem cell markers CD117 and CD15 in choroidal and ciliary body melanoma. Issue 3 (19th August 2015) - Lukenda, Adrian; Dotlic, Snjezana; Vukojevic, Nenad; Saric, Borna; Vranic, Semir; Zarkovic, Kamelija
Abstract : Aims: The aim of the present study was to immunohistochemically investigate the expression and prognostic significance of putative cancer stem cell markers CD117 (c-kit), CD34, CD20 and CD15 in a cohort of patients with primary choroidal and ciliary body melanoma. Methods: The immunohistochemical expression of these markers was evaluated using 3, 3′-diaminobenzidine tetrahydrochloride (DAB) and 3-amino-9-ethylcarbazole (AEC) chromogens on paraffin-embedded tissue samples from 40 patients who underwent enucleation in the period from 1985 through 2000. Thirty-one patients had adequate tissue specimens for the analysis. Results: CD117 overexpression was observed in 12 of the 31 samples (39%) when AEC chromogen was used and in 14 of 26 (54%) samples when DAB was used. CD15 positivity was seen in three out of 30 (10%) samples with AEC and in six out of 26 (23%) samples with DAB. CD20 and CD34 exhibited no positivity in the tested samples. During the average follow-up time of 8.7 years (range 0.5–22 years), 17 patients (55%) died due to metastatic disease. The Kaplan–Meier plots showed a significantly shorter overall and disease-free survival in CD117-positive patients when the AEC chromogen was used. CD15 expression was not associated with patients' survival. In multivariate analysis, patients expressing the CD117 AEC had 4.13 times higher risk of lethal outcome in comparison with CD117 AEC negative patients. Conclusions: Our retrospective cohort study has for the first time demonstrated a small proportion of CD15-positive uveal melanomas. CD117 AEC overexpression was associated with a worse outcome in patients with choroidal and ciliary body melanoma. Further studies should confirm the validity of these observations and their potential for targeted treatment modalities.